النشاط البدني ودوره في حماية الوظائف التنفيذية من التدهور المرتبط بالعمر: مقاربة نظرية تحليلية - Zhor Bejja; Atikka Bounou (Darul Yasin Al Sys, 2026)
Age-related cognitive decline represents one of the most significant health challenges in contemporary societies, with executive functions (EF) being among the most affected cognitive domains. This theoretical article aims to provide an integrative analytical framework for understanding the role of physical activity as a protective factor against age-related executive decline. The proposed approach rests on four pillars: first, reviewing epidemiological and experimental evidence from longitudinal studies, meta-analyses, and network meta-analyses that confirm the protective efficacy of physical activity; second, analyzing the neurobiological and physiological mechanisms underlying this protection, including structural and functional brain network changes as revealed by functional neuroimaging studies; third, discussing the quantitative dose-response relationship between exercise dose and protective response in light of Bayesian dose-response models; and fourth, comparing the relative effectiveness of different exercise modalities (aerobic, resistance, multicomponent, mind-body, and high-intensity interval training) in improving subcomponents of executive functions. Accumulated evidence indicates that regular physical activity enhances executive functions through multiple mechanisms including improved cerebral perfusion, increased release of neurotrophic factors, enhanced synaptic plasticity, and functional reorganization of brain networks associated with executive control, with distinct effect patterns emerging depending on exercise type, targeted executive subcomponent, age group, and clinical status. Studies also show that protective effects follow a nonlinear relationship with exercise dose, with optimal doses ranging between 670 and 1200 MET-min/week. The article concludes that physical activity constitutes a promising non-pharmacological strategy for preventing age-related executive decline, emphasizing the need to transition toward evidence-based personalized exercise prescriptions that account for individual differences in age, health status, and targeted executive components.